Characterization and Utilization of Rice Husk Ash (RHA) from Rice Mill of Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2009)
The characterization of Rice Husk Ash (RHA) was carried out using conventional chemical analysis and instrumental techniques. Chemical analysis reveals that RHA contains mainly silica along with minor inorganic oxides. Phase analysis by X-ray diffraction (XRD) indicates the presence of quartz, crystobalite and anorthite, while micro structural features obtained from Scanning Electron Microscopy (SEM) shows that RHA particles are highly porous and honeycombed structure. Thermal analysis indicates the presence of surface moisture. A wide range of particles (0.001-0.100 mm) are present in the sample with 59% below the size of 0.05 mm. However after characterization, utilization of RHA as a potential cost effective ingredient in developing a variety of construction materials (e.g. building brick, insulating brick and pozzolana cement) have been examined. The results obtained are very promising. Keywords : Charcterization, Rice husk ash, XRD, SEM, Construction material.   DOI: 10.3329/bjsir.v44i2.3666 Bangladesh J. Sci. Ind. Res. 44(2), 157-162, 2009